Pilot implementation of community health advocacy teams to improve the effectiveness of long-lasting insecticide net distribution through both campaigns and continuous channels in Ghana: a qualitative study of opportunities and barriers to implementation - Phyllis Dako-Gyeke; Ruby Hornuvo; Franklin N. Glozah; Emmanuel Asampong; Philip Teg-Nefaah Tabong; Adanna Nwameme; Gloria. M. Chandi; Nana Yaw Peprah; David Gittelman; Philip B. Adongo (Frontiers Media S.A., 2023)
IntroductionIn Ghana, the National Malaria Elimination Programme (NMEP) distributes long-lasting insecticide net (LLIN) to households for free through the periodic point mass distribution (PMD) campaign and continuous distribution to populations most vulnerable to malaria. It is known that the existence of effective and functional community-based groups could influence positive behaviours regarding health interventions promoted through health campaigns. However, there is no evidence of functional community-based groups that aim to improve the effectiveness of LLIN distribution campaigns by transitioning into primary healthcare delivery. This study aimed to explore the opportunities and barriers to the pilot implementation of co-created community health advocacy teams (CHATs) to improve the effectiveness of LLIN distribution through both campaigns and continuous channels in Ghana.MethodsA qualitative research approach was used among 43 CHAT members across six communities in the Eastern and Volta regions of Ghana. The CHAT constitutes significant community actors whose roles are centred on key elements of community/social mobilisation and capacity building, all nested in social and behaviour change communication (SBCC) strategies. The CHATs were pilot implemented in all study communities for 4 months after which we identified opportunities and barriers during implementation. CHAT members participated in six focus group discussions which were audio recorded, transcribed verbatim, and analysed thematically using the NVivo 13.ResultsCHATs were instrumental in sensitising community members through SBCC strategies. Moreover, there were changes in the behaviour of community members who were receptive towards and participated in CHAT activities. Community members were accurately informed about malaria (e.g., causes and preventive measures). However, the CHAT experienced barriers during implementation, including a lack of financial support to aid in transportation, organisation of meetings, and outreach activities. Additionally, the level of participation by CHAT members in activities and the medium of communication among members were key areas of concern.ConclusionThe CHATs would be instrumental in promoting LLINs' use during and after PMD campaigns through community outreaches. It is therefore necessary to provide resources to support their operations and a good network to address communication barriers. Finally, continuous capacity strengthening of CHAT members by the NMCP is important.